Some curricular challenges of citizen training and diversity in Chile - Manuel Silva Águila; Mónica Llaña Mena; Fabiola Maldonado García; Andrea Baeza Reyes (Pontificia Universidad Católica del Perú, 2018)
The article analyzes the complex relationship between cultural selection of curriculum and the diverse nature of the societies in which it is inserted. From a qualitative approach, we analyze the teachers' discourses of the Metropolitan Region about their representations on the political issues and the Politics and on the importance of curriculum and its possibilities for the attention to the diversity from the formation in citizenship. Results show the lack of problematization of diversity in this area. New contemporary phenomena such as valuing diversity require greater attention in the current processes of curriculum design for democratic coexistence.